THE IMPACT OF SOCIAL MEDIA USAGE TO ACADEMIC PERFORMANCE - Suita Allemina Gloria; Surya Akbar (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2019)
Background: Social media is basically a tool for someone to interact with other people with use of internet. In futher, social media is not only used as a tool for interact with others, but it can be used on learning process. This study aims to analyse correlation betwen duration of using a social media with academic performance.Method: This study used a cross sectional design. Respondents on this study are 126 undergraduates students on fourth years in Faculty of Medicine, Universitas Islam Sumatera Utara. Using of a social media are measured by how long a student use of a social media based on their purpose (learning or entertainment). Results from the measurement will grouping into two different group, that is using of a social media for learning group and for entertainment group. The academic performance was measured by calculating a Grade Point Average (GPA) of each student. The collected data were analyzed by using Spearman Correlation method.Results: There was a significant correlation betwen duration of using a social media for learning process with academic performance (r = 0,554, p = 0,0001). Similarly, there are a significant correlation betwen duration of using a social media for entertainment with academic performance (r = -0,568, p = 0,0001), but the coefficient correlation have a negative value.Conclusion: The social media have an impact to academic performance, where the students who used more social media as a learning process have a good GPA and the students who used more social media as a entertainment have a bad GPA. Sugesstions that can be given based on this study are the use of social media can be considered as a tool for helping students enhancing learning process.